Mesenchymal Stromal/Stem Cell (MSC)-Based Vector Biomaterials for Clinical Tissue Engineering and Inflammation Research: A Narrative Mini Review - Xue J; Liu Y (Dove Medical Press, 2023)
Junshuai Xue,1 Yang Liu2 1Department of General Surgery, Qilu Hospital of Shandong University, Jinan, People's Republic of China; 2Department of General Surgery, Vascular Surgery, Qilu Hospital of Shandong University, Jinan City, People's Republic of ChinaCorrespondence: Yang Liu, Department of General surgery, Vascular Surgery, Qilu Hospital of Shandong University, Jinan, Shandong, 250012, People's Republic of China, Tel +86 18560088317, Email liuyang_sdu@126.comAbstract: Mesenchymal stromal/stem cells (MSCs) have the ability of self-renewal, the potential of multipotent differentiation, and a strong paracrine capacity, which are mainly used in the field of clinical medicine including dentistry and orthopedics. Therefore, tissue engineering research using MSCs as seed cells is a current trending directions. However, the healing effect of direct cell transplantation is unstable, and the paracrine/autocrine effects of MSCs cannot be effectively elicited. Tumorigenicity and heterogeneity are also concerns. The combination of MSCs as seed cells and appropriate vector materials can form a stable cell growth environment, maximize the secretory features of stem cells, and improve the biocompatibility and mechanical properties of vector materials that facilitate the delivery of drugs and various secretory factors. There are numerous studies on tissue engineering and inflammation of various biomaterials, mainly involving bioceramics, alginate, chitosan, hydrogels, cell sheets, nanoparticles, and three-dimensional printing. The combination of bioceramics, hydrogels and cell sheets with stem cells has demonstrated good therapeutic effects in clinical applications. The application of alginate, chitosan, and nanoparticles in animal models has also shown good prospects for clinical applications. Three-dimensional printing technology can circumvent the shortage of biomaterials, greatly improve the properties of vector materials, and facilitate the transplantation of MSCs. The purpose of this narrative review is to briefly discuss the current use of MSC-based carrier biomaterials to provide a useful resource for future tissue engineering and inflammation research using stem cells as seed cells.Keywords: mesenchymal stromal/stem cells, vector biomaterial, tissue engineering, inflammation, cell transplantation